The Impact of Economic Integration on Regional Trade. The Case of the European Union - Milleville, Justyna (Regional Barometer. Analyses & Prognoses, 2009)
This paper examines the impact of the gradual integration of the European countries on the trade performance of the EU as a whole. Trade is an important factor in creating economic growth and it is significantly affected by the degree of economic liberalization. In this paper are analyzed both the successive stages of economic integration in Europe (in the period: 1960-2007) and the accompanying changes in trade structure and volume. The effects of integration on intra- and inter-EU trade are analyzed separately. The performance of the intra- and inter-industry trade and the position of the EU as a trade partner in the world economy are also described.